Tindak Tutur Direktif Pada Kolom Komentar Tiktok @Ayah Amanah Terkait Video Ustaz Hanan Attaki Yang Di Unggah Pada 3 Mei 2025 - Yani, Tri Suci Handa; Ningsih, Rika (UIR Press, 2026)
This study aims to analyze directive speech acts in the TikTok comment section of @ayahamanah related to Ustaz Hanan Attaki's video